The Relationship of Mother's Knowledge and Parenting Patterns with the Stunting Incident in Toddlers in the Loang Lembata Regency Public Health Centre Working Area - Katharina Laurentia Monika Nago Adja; Lilik Djuari; Ahmad Suryawan; Woro Setia Ningtyas (Green Publisher Indonesia, 2023)
Background: According to The World Health Organization (WHO) states that there are nutritional problems in toddlers, one of which is stunting , and lots of it found in a country one of them is developing in Indonesia, and still is becoming the main problem . National prevalence of stunting amounts to 26.9% and in 2021 it will be 24.4%. Is known that knowledge of mother and pattern foster care also becomes the reason for the occurrence of stunting. Purpose: To analyse the relationship between mother's knowledge and parenting patterns on the incidence of stunting in toddlers in the Loang Public Health Centre working area, Lembata Regency. Method: The type of research used is Observational Analytical. Population all mothers who have toddlers aged 12 – 59 months who live in the Loang Public Health Centre working area is 690 toddlers, a sample totalling 87 people. Taking samples using cluster sampling technique. The analysis used in research is chi-square analysis. Results: Based on the chi-square analysis test , it shows that there is a relationship between the level of maternal knowledge and the incidence of stunting among toddlers at the Loang Public Health Centre, Lembata Regency, p=0.001. Whereas for maternal parenting patterns variable found there is a relationship between maternal parenting patterns and the incidence of stunting among toddlers at the Loang Public Health Centre, Lembata Regency is p=0.008 Conclusion: Based on results research above concluded lower there was connection between mother knowledge and maternal parenting patterns with stunting incident